The Relationships Between Hardiness and Life Satisfaction or Expectation of Korean Multicultural Children: Focused on Mediating Effect of Acculturative Stress Moderated by Resilience - Kim, Bok-Hee; Suh, Kyung-Hyun (Frontiers in Psychology, 2021)
This study identified the relationship between hardiness and life-satisfaction or expectations of children from Korean multicultural families, and examined the mediating models of acculturative stress moderated by resilience on hardiness and life-satisfaction or life expectations. Participants in the study were 201 male and female children from Korean multicultural families. PROCESS Macro 3.5 Model 14 was used for analyses of moderating mediating effects. Results revealed that hardiness and resilience were positively correlated with life-satisfaction and life expectations, whereas acculturative stress was negatively correlated with life-satisfaction and life expectations of multicultural children. In a moderated mediating model for life satisfaction, there was no interaction effect of acculturative stress and resilience, but conditionally indirect effect of acculturative stress was only significant in groups with low resilience. In a moderated mediating model for life expectations, there was significant interaction effect of acculturative stress and resilience, and conditionally indirect effect of acculturative stress was only significant in groups with low resilience and with very high resilience. These findings suggest that only when multicultural children have low resilience, the mediating effect of acculturative stress is significant in relation of hardiness to life satisfaction, as well as hardiness and life expectations. In particular, resilience moderates the influence of acculturative stress on life expectations.